2016
DOI: 10.4103/1119-3077.179296
|View full text |Cite
|
Sign up to set email alerts
|

Duplex ultrasound: Indications and findings in a newly created facility at the University of Calabar Teaching Hospital, Calabar

Abstract: Duplex ultrasound has been shown to diagnose varied vascular pathologies even in a locale where it is a relatively new technique. It is recommended that timely referrals be made, and mobile Doppler units be acquired to save more lives and limbs in the developing world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Two hundred (200) patients were recruited, with a preponderance of males in our study (M:F=106:94). This was in sharp contrast to findings of a similar research by Salaam AJ et al [9] in which more females were scanned (M:F=59:67).The male predominance in our study is however in agreement with earlier studies by Olatunji AA [6] and Ikpeme A [31] which reported a male to female ratio of 29:13 and 51:25 respectively. This may just be coincidental, but most likely attributed to the increased incidence of vascular lesions in the males as reported by Michael H et al [34].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Two hundred (200) patients were recruited, with a preponderance of males in our study (M:F=106:94). This was in sharp contrast to findings of a similar research by Salaam AJ et al [9] in which more females were scanned (M:F=59:67).The male predominance in our study is however in agreement with earlier studies by Olatunji AA [6] and Ikpeme A [31] which reported a male to female ratio of 29:13 and 51:25 respectively. This may just be coincidental, but most likely attributed to the increased incidence of vascular lesions in the males as reported by Michael H et al [34].…”
Section: Discussionsupporting
confidence: 73%
“…There was no precise consistent percentage agreement with previous studies. However, DVT featured prominently as an important diagnostic Doppler finding in 13(31%), 9(12%) and 21(18.3%) patients scanned by Olatunji AA et al [6], Ikpeme A et al [31] and Salaam AJ et al [9] respectively. The lower values in their studies could be explained in part by the comparatively smaller sample size of 42,76 and 126 patients recruited respectively, compared to ours with 200 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thrombosis is a well-known disease that accompanies various pathological states. It frequently coexists with injuries of the pelvis, upper, and lower limbs [ 1 ]. It may also occur during immobilization, hospitalization, after accidents or procedures, such as venous catheterization, injections, or intravascular procedures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%